Clarence Darrow : attorney for the damned - Farrell, John A. (John Aloysius) (Doubleday, 2011)
Clarence Darrow is the lawyer every law school student dreams of being: on the side of right, loved by many women, portrayed by Spencer Tracy. His days-long closing arguments, delivered without notes, won miraculous reprieves. Darrow left a promising career as a railroad lawyer during the tumultuous Gilded Age in order to champion poor workers, blacks, and social and political outcasts against big business, Jim Crow, and corrupt officials. He became famous defending union leader Eugene V. Debs in the landmark Pullman Strike case and went from one headline case to the next--until he was nearly crushed by an indictment for bribing a jury. He redeemed himself defending schoolteacher John Scopes in the "Monkey Trial," cementing his place in history. Journalist John A. Farrell draws on previously unpublished correspondence and memoirs to offer a candid account of Darrow's divorce, affairs, feuds, tactics, and controversies.--From publisher description.